Tumor Suppressive Role of MUC6 in Wilms Tumor via Autophagy-Dependent β-Catenin Degradation - Liu, Bai-Hui; Liu, Gong-Bao; Zhang, Bin-Bin; Shen, Jian; Xie, Lu-Lu; Liu, Xiang-Qi; Yao, Wei; Dong, Rui; Bi, Yun-Li; Dong, Kui-Ran (Frontiers in Oncology, 2022)
Wilms tumor is the most common renal malignancy in children. Known gene mutations account for about 40% of all wilms tumor cases, but the full map of genetic mutations in wilms tumor is far from clear. Whole genome sequencing and RNA sequencing were performed in 5 pairs of wilms tumor tissues and adjacent normal tissues to figure out important genetic mutations. Gene knock-down, CRISPR-induced mutations were used to investigate their potential effects in cell lines and in-vivo xenografted model. Mutations in seven novel genes (MUC6, GOLGA6L2, GPRIN2, MDN1, MUC4, OR4L1 and PDE4DIP) occurred in more than one patient. The most prevalent mutation was found in MUC6, which had 7 somatic exonic variants in 4 patients. In addition, TaqMan assay and immunoblot confirmed that MUC6 expression was reduced in WT tissues when compared with control tissues. Moreover, the results of MUC6 knock-down assay and CRISPR-induced MUC6 mutations showed that MUC6 inhibited tumor aggression via autophagy-dependent β-catenin degradation while its mutations attenuated tumor-suppressive effects of MUC6. Seven novel mutated genes (MUC6, GOLGA6L2, GPRIN2, MDN1, MUC4, OR4L1 and PDE4DIP) were found in WT, among which MUC6 was the most prevalent one. MUC6 acted as a tumor suppressive gene through autophagy dependent β-catenin pathway.